Baseline results from EUROMOD: 2006 - 2009 policies - Silvia Avram; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2012)
The aim of the paper is to provide a description of the latest public release of EUROMOD (version F5.0), a microsimulation model of taxes and benefits in the EU. After giving a brief account of the process of constructing EUROMOD, we present headline indicators for income inequality and risk of poverty using EUROMOD and discuss explanations for differences between these and EU- SILC based indicators. We then compare EUROMOD indicators across countries and as policies evolve across time between 2006 and 2009. Throughout we highlight both the potential of EUROMOD as a tool for policy analysis and the caveats that should be borne in mind when using it and interpreting results.
Keywords: C15; H24; H55; I3; 330; microsimulation; redistribution; tax-benefit system; poverty; inequality